The 18-month efficacy of an Intensive LifeStyle Modification Program (ILSM) to reduce type 2 diabetes risk among rural women: a cluster randomized controlled trial - Qinyi Zhong; Yao Chen; Mengchun Luo; Qian Lin; Jianghong Tan; Shuiyuan Xiao; James Allen Willey; Jyu-Lin Chen; Robin Whittemore; Jia Guo (BMC, 2023)
Abstract Background Many lifestyle interventions have demonstrated efficacy up to one-year follow-up, yet maintaining improvements at longer-term follow-up is a well-recognized worldwide challenge, especially in underserved areas. The purpose of this study is to compare the 18-month efficacy of an Intensive LifeStyle Modification Program to usual care in reducing the risk for type 2 diabetes (T2D) among women with a history of gestational diabetes mellitus (GDM). Methods We conducted a two-arm, cluster randomized controlled trial among women with a history of GDM in China. A total of 16 towns (clusters) in two distinct rural areas in south-central China were randomly selected (8 towns per area) and assigned (1:1) to the intervention (Intensive LifeStyle Modification Program) or control (usual care) group with stratification in the two rural areas. The strategies for maintaining intervention effects were used (including setting recursive goals and providing a supportive environment, etc.) under the guidance of social cognitive theory. The primary outcome was a change in T2D risk; secondary outcomes included glycemic, weight-related, behavioral, and psychological variables. All outcomes were collected at baseline, 6, and 18 months. All participants entered the intention-to-treat analysis. Data were analyzed via generalized estimation equation models (accounting for clusters) at the individual level, with subgroup analysis included in the model. Results The sample included 320 women from 16 clusters (20 women per cluster). At 18 months, the intervention group demonstrated a significant improvement in T2D risk score, fasting blood glucose, body mass index (BMI), waist circumference, intention to eat low glycemic index food, perceived stress, quality of life in psychological and environmental domains, and social support over time (p < 0.05) based on the intention-to-treat analysis set. Subgroup analysis showed a significant interaction effect on T2D risk score in subgroups of different BMI, waist circumference, and blood glucose (p < 0.05). Conclusions Over 18 months, the Intensive LifeStyle Modification Program reduced T2D risk among rural women with a history of GDM in China. Women who were overweight, had high abdominal adiposity, or had blood glucose intolerance benefited more from this intervention. This program serves as a potential diabetes prevention model for women with a history of GDM in low-resource settings worldwide. Trial registration Registered on Chinese Clinical Trial Registry (ChiCTR1800015023) on 1st March 2018, http://www.chictr.org.cn/showproj.aspx?proj=25569